SHALAT DHUHA DAN PENGUATAN KARAKTER PESERTA DIDIK - Alivermana Wiguna; Fatimah Setiani; Jayadi Jayadi; Agus Heriyanto (STKIP MUHAMMADIYAH SAMPIT, 2021)
There is an interesting phenomenon in mushalla Al-Kautsar MAN Kotawaringin Timur, Central Kalimantan at each first break. Not a few students and students come to the mushalla to perform Dhuha prayer, which is one of the sunnah prayers performed around the sun begins to rise until the time of Dhuhr. The students came one by one to the mushalla, took ablution water and performed Dhuha prayers between two and eight rak'ahs. This phenomenon shows the growth and development of students' spiritual attitudes, which at the next level grow and develop also the social attitudes of students. So that the strength of character of the students of MAN Kotawaringin Timur. The issues raised in this study are: first; what is the motivation of students to perform Dhuha prayers. Second; what character strengths appear in students after diligently performing Dhuha prayers? The methodology used in this study relies on the paradigm of social definition, with verstehen (interpretative understanding) method. While the approach used is phenomenological approach. The results of this study showed that the motivation of students to perform Dhuha prayers include: to draw closer to God, to feel calm, to refresh the body. The strength of character that arises include: courage, integrity, hope, vitality, and spirituality.